Ab-Initio Predictions of the Energy Harvesting Performance of L-Arginine and L-Valine Single Crystals - Guerin, Sarah (Frontiers in Mechanical Engineering, 2021)
Biological piezoelectric materials are beginning to gain attention for their huge potential as eco-friendly energy harvesting materials. In particular, simple amino acid and peptide crystal assemblies are demonstrating large voltage outputs under applied force, and high sensitivity when detecting vibrations. Here we utilise Density Functional Theory (DFT) calculations to quantitatively predict the energy harvesting properties of two understudied proteinogenic amino acid crystals: L-Arginine and L-Valine. The work highlights the ability of quantum mechanical calculations to screen crystals as high-performance energy harvesters, and demonstrates the capability of small biological crystals as eco-friendly piezoelectric materials. L-Arginine is predicted to have a maximum piezoelectric voltage constant of gij = 274 mV m/N, with a Young’s Modulus of E = 17.1 GPa. L-Valine has a maximum predicted piezoelectric voltage constant of gij = 62 mV m/N, with a calculated Young’s Modulus of E =19.8 GPa